Design, synthesis and biological activity of 3-pyrazine-2-yl-oxazolidin-2-ones as novel, potent and selective inhibitors of mutant isocitrate dehydrogenase 1 - Ma, Tianfang; Pusch, Stefan; Deimling, Andreas von (Bioorganic & medicinal chemistry, 2017)
Isocitrate dehydrogenases (IDHs) catalyze the oxidative decarboxylation of isocitrate to alpha-ketoglutarate (α-KG) generating carbon dioxide and NADPH/NADH. Evidence suggests that the specific mutations in IDH1 are critical to the growth and reproduction of some tumor cells such as gliomas and acute myeloid leukemia, emerging as an attractive antitumor target. In order to discovery potent new mutant IDH1 inhibitors, we designed, synthesized and evaluated a series of allosteric mIDH1 inhibitors harboring the scaffold of 3-pyrazine-2-yl-oxazolidin-2-ones. All tested compounds effectively suppress the D-2-hydroxyglutarate (D-2-HG) production in cells transfected with IDH1-R132H and IDH1-R132C mutations at 10μM and 50μM. Importantly, compound 3g owns the similar inhibitory activity to the positive agent NI-1 and shows no significant toxicity at the two concentrations. The parallel artificial membrane permeation assay of the blood-brain barrier (PAMPA-BBB) identified 3g with a good ability to penetrate the blood-brain barrier (BBB). These findings indicate that 3g deserves further optimization as a lead compound for the treatment of patients with IDH1 mutated brain cancers.